2016
DOI: 10.1155/2016/6569103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Small Bowel Obstruction Caused by Bezoars Using Risk Factor Categories on Multidetector Computed Tomographic Findings

Abstract: Objectives. The aim of this study was to detect factors associated with small bowel obstruction (SBO) caused by bezoars on multidetector computed tomographic findings. Methods. We retrospectively reviewed 61 patients who had bezoars in the small bowels on MDCT. The patients were divided into SBO patients group and non-SBO patients group. The mean values of the diameter, volume, and CT attenuation as well as location and characteristics of the bezoars were compared between the two groups. Multivariate analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…For evaluating whether SBO was present and obstruction severity, there were no differences among the three protocols with respect to diagnostic self-confidence, agreement, detection rate, and accuracy. These results are consistent with previous findings[5,6,13,14,19,20] and suggest that the conventional axial and coronal reformations may be sufficient to evaluate whether SBO is present and the obstruction severity without the need for additional post-processing techniques.…”
Section: Discussionsupporting
confidence: 92%
“…For evaluating whether SBO was present and obstruction severity, there were no differences among the three protocols with respect to diagnostic self-confidence, agreement, detection rate, and accuracy. These results are consistent with previous findings[5,6,13,14,19,20] and suggest that the conventional axial and coronal reformations may be sufficient to evaluate whether SBO is present and the obstruction severity without the need for additional post-processing techniques.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from indigestible food consumption or presence of foreign objects, many risk factors have also been described that facilitate the development of bezoars, including diabetes mellitus, hypothyroidism, inability to chew food, history of abdominal surgery, gastrointestinal dysfunction, and drugs [ 4 , 5 ]. Although a bezoar can enter the small intestine, incarceration may occur when the diameter of a bezoar is >2.5 cm, thereby causing small bowel obstruction [ 6 ]. It is worth noting that in one of our pediatric cases, small bowel obstruction occurred due to the presence of a 2.0 cm diameter bezoar, indicating that the presence of the obstruction caused by bezoars may be related to individual differences among patients.…”
Section: Discussionmentioning
confidence: 99%
“…They can be seen with abdominal radiography, ultrasonography, or CT as a mass or a filling defect. A recent study of bezoars in China by Kuang et al examined risk factors for small bowel obstruction caused by bezoars and found that major diameter measured on CT scans was a significant independent predictor [ 7 ]. In general, bezoars most commonly occur in the distal small intestine or the jejunum and in some cases, are associated with Meckel's diverticula in the ileum [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of bezoars in China by Kuang et al examined risk factors for small bowel obstruction caused by bezoars and found that major diameter measured on CT scans was a significant independent predictor [ 7 ]. In general, bezoars most commonly occur in the distal small intestine or the jejunum and in some cases, are associated with Meckel's diverticula in the ileum [ 7 ]. The radiographic appearance of the bezoar on CT scan may be similar to the fecalized small bowel content seen with established small bowel obstructions ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%